AB0191 Anti-ssa and anti-jo1 levels in interstitial lung disease related to idiopathic inflammatory myopathies. (12th June 2018) - Giannini, M.; Tampoia, M.; Abbracciavento, L.; Girolamo, F.; Lia, A.; Mascolo, E.; D'Abbicco, D.; Coladonato, L.; Iannone, F.
Abstract : Background: The lung is the most frequently involved extramuscular organ in idiopathic inflammatory myopathies (IIMs); the most common form of lung involvement is interstitial lung disease (ILD). Some autoantibodies are strongly associated with ILD and with specific phenotypes and prognosis of ILD. Among myositis-specific auto-antibodies (MSAs), antibodies against aminoacyl-tRNA-synthetases (AsAb) are the strongest predictive factors for ILD, and anti-Jo-1 is the most common AsAb. Among myositis-associated auto-antibodies (MAAs), anti-SSA/Ro52 is frequently found in sera of patients with IIM and ILD, often associated with anti-Jo-1. The coexistence of anti-SSA/Ro52 and anti Jo-1 seems to be related to a more severe and extensive pulmonary fibrosis with higher score in HRCT compared with the patients with only anti-Jo-1 antibodies. Furthermore, some reports suggest that presence of anti-Jo-1 could be a biomarker for good prognosis 1 . The significance of antibodies levels for the prognosis of ILD in IIMs was not widely investigated. Objectives: To investigate the relationship between antibody levels and clinical manifestations, laboratory data, pulmonary function tests (PFTs), disease activity indices in ILD associated to IIMs. Methods: Among 130 IIMs admitted to Rheumatology Unit of Bari from January 2010 to January 2018, we retrospectively examined 49 patients (40 F; 22 PM, 25 DM, 1 IBM; mean age at ILD onset 51 years, range: 23–83) because of ILD defined by high resolution computed tomography (HRCT). Clinical manifestations, laboratory data, HRCT pattern, PFTs (FVC, FEV1 and DLCO), therapy, disease activity as Manual Muscle Test (MMT-12), Health Assessment Questionnaire (HAQ), Physician Global Assessment (PGA) at ILD onset, were obtained from medical records. Ferritin levels and autoantibodies were detected in serum samples collected at ILD onset. ANA were tested by IIF on HEp-2 cell substrates, MSAs (JO1, EJO, OJ, PL7, PL12, SRP, HMGCR, Mi2, TIF1γ, MDA5, NXP2, SAE) and MAAs (Ro52, Ku, PM/Scl 75–100, RNP, Scl70) by line-blot method. Anti-SSA and anti-Jo1 were also detected by CLIA method. Correlation analysis were run using parametric and non-parametric test according to data distribution. Results: 45 of 49 (91, 8%) patients were positive for MSAs and/or MAAs. 40 of 45 (88%) were positive at least one of MSAs. The double presence of MSAs and anti-Ro52 was observed in 21 of 40 (52, 5%), showing anti-Jo1/SSA in most cases (15/21, 71, 4%). Among all correlations studied between anti-Jo1 or anti-SSA levels and PGA or PFTs, we found a significantly correlation between anti-Jo1 and PGA (p=0, 03, R=0, 46). We didn't find significantly correlation between autoantibodies and ferritin serum levels. Conclusions: These findigs confirm that ILD was associated with autoantibodies positivity. Further studies in larger cohort need to investigate if autoantibodies levels have a prognostic role in global outcome. Unlikely some controversial works in literature, serum ferritin does not seem a biomarker of severity of lung involvement in IIMs. Reference: [1] Labirua A, et al. Interstitial lung disease and idiopathic inflammatory myopathies: progress and pitfalls. Curr Opin Rheumatol2010. Disclosure of Interest: None declared